Applied perspective - Hardy, Walter Eugene (My University, 1898)
Introduction: The most obvious relations of visible objects are those of magnitude and distance. The connection between apparent magnitude and distance is one of the questions learned in infancy. The laws that govern this relation involve profound mathematical principles. The art of representing solids on a plane surface is known as perspective. Of the laws of perspective, antiquity had but little knowledge. Lucretius, observing the effects of aerial perspective and kindred phenomena, sought by ingenious explanations to account for them through his septum of materialistic philosophy. But even without knowledge of the principles of projection, so accustomed are we to adjust our ideas of size to our perceptions of apparent distance that a Chinese landscape, with its notable lack of perspective is to us quite confused and unintelligible.
Citation: Hardy, Walter Eugene. Applied perspective. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Magnitude; Distance; Mathematical Principles; Laws; Chinese Landscape; Theses; Manuscripts (documents)